Antihyperlipidemic and Haematological Effect of Triherbal Formulation on Triton1339-Induced Hyperlipidemic Rats - Umaru, Isaac John; Ejeh, Yakubu Ojochenemi; Shaibu, Isaac Eleojo; Yemisi, Adeyanju Kate; Talent, Akoh Miracle; Enyojo, Lawal Favour (African Journal of Biochemistry and Molecular Biology Research, 2025)
Hyperlipidemia is one of the principal factors underlying the risk for cardiovascular disease. Confirmatory evidence from animal, clinical, and epidemiological studies has clearly established the positive correlation. Allopathic antihyperlipidemic drugs are available but the side effects and contraindications. However, this study was designed to determine the haematological and antihyperlipidemic effect of ethanol leaf extract of triherbal formulation (Mucuna pruriens, Phyllantus amarus, Securidaca longipeduculata) in wistar rat as a cheaper and readily available alternative. 46rats were grouped into normal, diseased, standard drug controls and test groups with seven rats each. quantitative phytochemical, haematological and antihyperlipidemic analysis were carried out according to standard methods. Results revealed presence of saponin, alkaloids, tannin, flavonoids, cardiac glycosides, phenolic with Total phenol exhibiting the highest values haematological results showed improving activities of the formulation on the erythrocytes, heamoglobins, lymphocytes and neutrophiles, this confers good effect on heamatological and immonological parameters especially at higher dose. In antihyperlipidemic activities, triherbal formulation significantly (p≤0.05) decrease the level of TC, TAG, LDL and improve upon HDL in both serum and liver homogenate effects thought to be via inhibition of cholesterol biosynthesis, absorption modification of lypogenic and lipolitic enzymes. Conclusively, the studies indicated triherbal formulation contain bioactive compounds with diverse biological activities such as immunomodulatory, inflammatory, heamatological and lipid profile regulating activities.